Evolução das qualidades física e fisiológica da semente de soja no beneficiamento - Moreano, Tana Balesdent (2012)
Seed processing is an essential step on high quality seed production, once the elimination of inert materials, weed seeds, and non-standard seeds allow maintaining the seed quality obtained in the field. The initial quality of a seed lot depends on the cultivar, on the weather conditions of the agricultural year and on good managing of the harvest machines. The final quality, however, is attributed to the care provided during processing and storage and to minimization of injuries, which may occur during the processing procedures. The objective of this study was to assess the evolution of physical and physiological characteristics of soybean seeds during two growing seasons (2009/1010 and 2010/2011), in a Seed Processing Plant. In the first growing season, seed samples of a set of soybean cultivars were collected along the processing line. Therefore, samples of six soybean cultivars were collected, while seeds were passing through each processing machine, totaling 15 sampling points: 1) bin; 2) entry of the air-screen machine; 3) exit of the air-screen machine; 4) entry of the spiral separator; 5) exit of the spiral separator and entry of the size grader; 6) size grader (6.5 mm seed size); 7) exit of the size grader (5.5 mm seed size); 8) entry of the gravity separator (6.5 mm seed size); 9) entry of the gravity separator (5.5 mm seed size); 10) exit of the gravity separator (6.5 mm seed size); 11) exit of the gravity separator (5.5 mm seed size); 12) holding bin (6.5 mm seed size);13) holding bin (5.5 mm seed size); 14) bagging scale (6.5 mm seed size); and 15) bagging scale (5.5 mm seed size). A completely randomized experimental design was used, with the treatments arranged in a 15 x 6 factorial scheme (15 sampling sites x 6 cultivars), with 10 replications. The following physical characteristics were assessed in the first year: 1 - moisture content; 2 - impurity percentage; 3 - apparent specific mass; and 4 - mass of 1,000 seeds. The variables used for assessing seed physiological quality were: 1) germination; 2) vigor - accelerated aging test; 3) viability by the tetrazolium test (TZ), classes 1 to 5; 4) vigor (TZ), classes 1 to 3; 5) weathering damages (TZ), class 3; 6) total mechanical damages (TZ), classes 1 to 8; and 7) damages caused by stink bugs (TZ), classes 1 to 8. In the second agricultural year, samples of two soybean cultivars were collected before and after the passage of seeds through five processing machines: air-screen machine; spiral separator, size grader; gravity separator (6.5 mm seed size); and gravity separator (5.5 mm seed size), with 20 replication for each sampling point. In the second experiment, the mass of 1,000 seeds was assessed and also the same variables for physiological characteristics, assessed in the first experiment; in addition, the lethal mechanical damages (TZ classes 6 to 8) were also evaluated. According to the results, processing improves physical and physiological characteristics of soybean seeds and its efficiency is accentuated in seeds with intermediate quality. The conveying system (elevators and conveyor belts), once well designed in the project and with transportation speed specifically for seeds, which is 45 meters per minute, does not interfere in the enhancing of mechanical damages to the seeds. Seeds with mechanical damages tend to concentrate at larger sizes; and seeds presenting stink bug damages tend to concentrate at smaller sizes. Seeds presenting weathering damages are not eliminated in whatever processing steps. The gravity separator plays an essential role in improvement of physical and physiological attributes of seed lots, by allowing lower density seeds to be discarded and by removing partly seeds with mechanical and stink bug damages.